Conduction Abnormalities After Transcatheter Aortic Valve Replacement - Somsupha Kanjanauthai; Kabir Bhasin; Luigi Pirelli; Chad A Kliger (US Cardiology Review, 2019)
Transcatheter aortic valve replacement (TAVR) has been established as a therapeutic option for patients with severe symptomatic aortic stenosis who are of intermediate or higher surgical risk. Several periprocedural complications are reduced with newer transcatheter heart valve generations; however, conduction abnormalities and the need for permanent pacemaker implantation have remained unchanged and are the most frequent TAVR complications. The close relationship of the atrioventricular node and left bundle branch to the subaortic region explains these potential conduction abnormalities. This article highlights conduction abnormalities after TAVR with a focus on basic conduction system anatomy in relation to the aortic valve, the mechanism, incidence, predisposing factors for occurrence, impact on mortality and finally, proposed treatment algorithms for management.